Developing Students' Reading Comprehension in Hortatory Exposition Text by Using Questioning Technique in SMAN 13 Medan in Academic Year 2022/2023 - Henny, Indria; Harianto II (International Journal of Educational Research Excellence (IJERE), 2023)
This study aims to determine the development, validity and effectiveness of the Developing reading comprehension material by using questioning technique at SMAN 13 Medan. This research is a research and development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The instrument used is a questionnaire for expert lecturers and students, interviews with teachers, and the results of the last test given to students. The test results from the validator through media design as a whole get valid category criteria (88,9 %) so that teaching materials can be used as teaching materials for students in the learning process. The results of the assessment of English Teaching Materials by experts on the substance of the material as a whole from the aspects that are considered to have received appropriate criteria (86,7%). so that the Teaching Materials can be used in the learning process. And the test results show that the average value of students with score 62,70 % so that they get the effective criteria.